Perioperative and posttraumatic anti-edematous decongestive device-based negative pressure treatment for anti-edematous swelling treatment of the lower extremity - a prospective quality study - Dresing, Klaus (Int J Burns Trauma, 2021)
Background: The perioperative management of trauma cases and orthopedic procedures is negatively influenced by tissue swelling and edema. They delay surgical treatment, extend stay in hospital and prolong the overall time of convalescence. In case of traumatic or postoperative edema the limited transport capacity (missing muscle pump and destruction of lymphatic channels) is casual. Edema mostly results in pain, limited function of the extremity, change in shape, higher infection rate and wound disorders. Manual lymph drainage (MLD) is a treatment option with respect to the complex physical decongestion (CPD). Objective: To evaluate whether a device-based negative pressure lymph drainage (NPLD) is capable of reducing posttraumatic and perioperative swelling of the lower extremity effectively and sustainably. Methods: Prospective quality study submitted to the Ethics Committee. The patients only received the procedures after signing the informed consent. The negative pressure was applied locally by using LymphaTouch® device (LT) (FDA approved) with a silicone-coated applicator. The lymphatic drainage had been either applied by a local stationary manner or by using the “Lift + Twist” technique. A negative pressure has been adjusted between 50-250 mm Hg depending on the skin and tissue texture. The frequency was chosen between 90-70 Hz. Type of application: pulsed or continuous negative pressure treatment. The procedure always began in the supraclavicular fossa and continued until reaching the area of surgery in the lower extremity. Duration approx. 30 min. The patient was encouraged to drink fluids after the LymphaTouch treatment (LTT). The results were documented by measurement of the girth and movement according to neutral-zero-method (NZM) and photographs. Statistics: Multi-variance, Wilcoxon test non-parametric. Inclusion criteria: Patients with injury to the lower extremity (LE), elective patients, age > 18 years, signed informed consent. Results: 101 patients with injuries/surgical interventions to the lower extremity, age: 64.9 ± 13.17 years. The swelling was more pronounced at the knee. After 4 treatments, there was a measurable decrease in swelling of 11.6% at the lower extremity. In patients with trauma to the hip joint or hip interventions, the swelling at the femur was reduced by 8.6% between LTT 0 vs. 4. In patients with trauma to the knee joint and surgical interventions, significantly more female patients showed a positive effect to LTT. The mobility improved substantially, while the level of pain decreased. The patients reported immediate pain relief. No complications occurred. Conclusion: The perioperative and posttraumatic swelling at the lower extremity can be positively affected by the LT-NPLD within the first days. The preoperative duration until surgical intervention was decreased. The postoperative stage of wound and soft tissue swelling was reduced.